Immunotherapeutic approaches in triple-negative breast cancer: latest research and clinical prospects - John Stagg; Bertrand Allard (Therapeutic Advances in Medical Oncology, 2013)
Triple-negative breast cancer (TNBC), as defined by the absence of estrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 expression, is a challenging disease with the poorest prognosis of all breast cancer subtypes. Importantly, there are currently no known molecular targets for this subgroup of patients. Recent advances in genomics and gene expression profiling have shed new light on the molecule heterogeneity of TNBC. We present an overview of the scientific evidence suggesting that clinical outcome in TNBC is affected by tumor-infiltrating immune cells. We also describe tumor-associated antigens recently identified in TNBC. Finally, we review the current literature on promising immunotherapies for TNBC, including tumor vaccine approaches, immune-checkpoint inhibitors, antagonists of immunosuppressive molecules and adoptive cell therapies. It is our contention that selected patients with TNBC with lymphocytic tumor infiltrates at diagnosis may benefit from immune-based therapies and that these immunotherapies will be most beneficial in combination with cytotoxic drugs that potentiate adaptive anti-tumor immunity.